P111 Paediatric day-case adeno-tonsillectomy transfer to Hospital-in-the-Home: a new model of care. (9th November 2022) - Simpson, C; Holt, M; Withers, A; Smith, A; Inglis, E; Morrison, S; Phillips, D
Abstract: Aims: Tonsillectomy and adenoidectomy (T&A) is one of the most common paediatric surgical procedures. Post-operatively, children are monitored in hospital for bleeding, SpO2 desaturation, pain and oral intake. We report a new model of care for low-risk children undergoing T&A to transfer to hospital-in-the-home (HITH) on the day of surgery, with the benefits of providing medically-supported recovery at home and reducing healthcare expenditure. Methods: Children >/= 5yr, with normal pre-operative overnight oximetry, without co-morbidities/post-operative upper airway obstruction/bleeding and tolerating oral intake were eligible for HITH, between 4-6hr post-T&A. Families were educated on administering adequate pain relief and oral intake. Overnight oximetry was monitored on the first night. Patients were reviewed at home day 1 then via telehealth day 2, before discharge. Results: Sixteen patients with mean age 8.2yr (5-13yr) transferred to HITH post-day-case T&A. There were no episodes of desaturation, bleeding or readmission. One patient presented to Emergency day 1 with fever, pain and vomiting, received symptomatic treatment and transfer back to HITH, with discharge day 2. Two patients required one additional telehealth assessment of hydration (1) and pain control (1) on day 3, before discharge. Conclusions: This new model of care provides a safe, cost-saving, supported management pathway for low risk paediatric post-T&A cohorts. Eligibility criteria will now expand as we increase virtual monitoring in the low risk cohort, freeing up HITH beds for younger and more complex post T&A patients, and hospital beds for higher risk patients, enabling greater throughput for overwhelmed surgical wait lists.